Accounting Profit, Leverage, and Firm Size on Stock Prices in the Indonesia Stock Exchange - Fintha Rahmakasih; Wa Ode Rayyani (Penerbit Goodwood, 2025)
Purpose: This study examines the influence of accounting profit, leverage, and firm size on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange, a question that remains relevant as Indonesia's capital market continues to navigate post-pandemic volatility, shifting benchmark interest rates, and inflationary pressure through 2026.Methodology: A quantitative research design was applied using secondary data drawn from audited annual financial statements covering the 2019 to 2023 period. Purposive sampling produced 87 firms that satisfied the sample selection criteria, generating 435 firm-year observations, which were analyzed through panel data regression rather than ordinary multiple regression so that both cross-sectional and time-series properties of the data could be captured.Results: Model specification tests, namely the Chow test and the Hausman test, indicated that the Fixed Effect Model was the most appropriate estimator. The regression results show that accounting profit exerts a positive and significant effect on stock price, leverage exerts a negative and significant effect, and firm size exerts a positive and significant effect, with an adjusted R square of 0.609. Conclusions: All three fundamental variables jointly shape stock price movement in a manner consistent with signaling theory and agency theory. Limitations: The model does not incorporate macroeconomic variables such as interest rates, exchange rates, or inflation.Contributions: The findings offer investors and corporate managers an updated, evidence-based reference for building investment portfolios and financing policies grounded in current fundamental financial ratios.